Peningkatan kesadaran masyarakat terkait bahaya stunting melalui serangkaian edukasi dan sosialisasi di Desa Rantau Bais - Mutiara Amelia; Fitri Diani; Ulfah Hana Damayanti; Jeshica Rahayu Putri; Denas Prayoga; Hikmatul Hasyanah; Parolan Sitohang; Glori Miracle; Vica Mevana Anthika Nainggolan; Nur Alya Gianry Dwi Putri (Unri Conference Series: Community Engagement, 2022)
Stunting is an issue that often gets the attention of the public and the government. Stunting is defined as a condition of failure to grow and develop a child due to several factors such as lack of nutritional intake, unhealthy lifestyle to untrained motor skills. In this case, have been done steps by conducting a series of education, namely Clean and Healthy Lifestyle (PHBS) training and motor and locomotor movements and socialization with Rantau Bais village staff about “Handling and Prevention of Stunting for Mother and Child”. The method used was qualitative field study. The result was an increasing childrens ability to apply a healthy lifestyle as a routine and increasing public knowledge and awareness about stunting.